Verbal Expression Disorder Moon Sang Tae Character: Person With Autism in Korean Drama It's Okay Not To Be Okay (Psycholinguistic Study) - Ami Bunga Wulandari; Reni Kusmiarti; Manila Agustina (International Journal Labs, 2024)
In psycholinguistic studies, there is discussion regarding verbal expression disorders, a person's inability to use language to express their feelings. This research aims to analyze and describe forms of verbal expression disorders in utterances from people with Autism, such as the character Moon Sang Tae in the Korean drama It's Okay Not to Be Okay. For this purpose, researchers used descriptive qualitative research. The data analyzed comes from two sources, namely primary data sources in the form of utterances of the character Moon Sang Tae from the Korean drama It's Okay to Not Be Okay and secondary data sources in the form of scientific journals, proceedings, articles and books related to relevant psycholinguistics. With the research topic raised. Data was collected by listening to the drama and noting essential things related to verbal expression disorders. The results of language disorders due to the autism spectrum experienced by the character Moon Sang Tae in the Korean drama Its Okat to Not Be Okay are 183 data, divided into 50 data on social interaction disorders, 62 data on communication disorders and 71 data on behavioural pattern disorders.